Relationship with supervisor and role clarity on employee performance moderated by achievement motivation - Hidayati, Tetra; Hudayah, Syarifah; Putit, Lennora (International Journal of Management and Sustainability, 2025)
This study aims to explore the link between supervisors and role clarity toward employee performance, with achievement motivation serving as a moderating variable. The study was conducted at PT Kayu Lapis Asli Murni, a company in the plywood processing sector. A quantitative methodology was employed, and primary data were collected through questionnaires administered to 177 technical employees. The data analysis method used in this study employs Structural Equation Modeling with Partial Least Squares (SEM–PLS). The results indicate that a strong relationship with supervisors, combined with role clarity, fosters optimal employee performance. Conversely, achievement motivation does not moderate the relationship between supervisors and employee performance; however, it can moderate the causal link between role clarity and employee performance. Role clarity provided by supervisors can significantly enhance employee performance by helping employees understand the expectations and responsibilities they must fulfill. This positive impact is further amplified when employees possess high achievement motivation, as they are more inclined to utilize this clarity to achieve optimal work results. The study's results enhance both the theoretical understanding and practical implications of organizational behavior by showing that the relationship between supervisor support and role clarity in employee performance is influenced by achievement motivation. This finding underscores the importance of integrating contextual and personal factors into performance models. Additionally, the results support motivation and leadership theories by introducing moderating elements that amplify the effects of situational variables on work outcomes.